Grisel's Syndrome: A Masquerader of Torticollis with a Hidden Atlanto-Axial Dislocation Agenda - Goh, Eyrique; D., Pathmarooban; R., Alif F. (Journal of Child Science, 2021)
Torticollis is a rather common presentation in pediatrics, with common etiologies. This is a rare presentation of a spinal pathology secondary to an underlying infection of the head and neck region causing anomalous head position masquerading as a torticollis. Painful torticollis, or abnormal head position described as “cock-robin head” position in children, draws attention. Grisel's syndrome (GS) is an inflammatory condition of a nontraumatic atlantoaxial rotatory subluxation or fixation (AARS/F). Diagnosis is derived clinically with radiological confirmation. The aim of this report is to raise attention of positional masquerade during intervals of radiographs, leading to the delay in diagnosis and heighten awareness of this syndrome that is needed to derive the diagnosis. In this case, the patient initially presented to the institution with a radiograph that had shown no overt abnormality and was requested for further detailed imaging, but the child's parents had refused. Upon a revisit to the clinic due to worsening of symptoms, a repeated radiograph was taken, a clear AARS was detected, and proceeded with a computed tomography (CT) cervical imaging to confirm the subluxation. The CT scan showed an overt subluxation with significant narrowing of the cord spaces with a retropharyngeal abscess. Otolaryngology and Spine services were consulted, and a surgical option was offered. However, the parents refused surgery and proceeded conservatively with antibiotics and a cervical halter. Early diagnosis and early treatment is fundamental to a better prognosis. Presence of GS is associated with late recovery in comparison to non-Grisel's causes of AARS/F. A treating surgeon should be aware of this condition and recognize it based on the “cock-robin” head position in absence of a triggering trauma with an underlying inflammatory pathology of the head and neck region. Presence of concomitant infection with AARS/F and Fielding and Hawkins classification types are prognostic factors for late recovery.
Keywords: Grisel's syndrome; atlantoaxial rotatory subluxation; atlantoaxial rotatory fixation; atlantoaxial instability; retropharyngeal abscess; cock robin; torticollis